2013
DOI: 10.1007/s40291-013-0060-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simultaneous Detection of Vitamin D Receptor Gene Polymorphisms by a Single ARMS-PCR Assay

Abstract: As ARMS-PCR is more rapid, economic, and user friendly than PCR-RFLP, its substitution would be welcomed in disease association and pharmacogenetic studies of VDR variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…These results reflect higher accuracy of PCR-RFLP compared to T-ARMS-PCR, which results were consistent with the study by Li et al (2014). Based on sequencing experiments, the calculated accuracy of T-ARMS-PCR and PCR-RFLP reached 99.07% and 99.69%, respectively, which was very similar to the previous results Berenstein et al, 2014;Jafari et al, 2014). Therefore, T-ARMS-PCR is a reliable method for genotyping of SNP g.2885CNA within bovine ACADVL gene.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results reflect higher accuracy of PCR-RFLP compared to T-ARMS-PCR, which results were consistent with the study by Li et al (2014). Based on sequencing experiments, the calculated accuracy of T-ARMS-PCR and PCR-RFLP reached 99.07% and 99.69%, respectively, which was very similar to the previous results Berenstein et al, 2014;Jafari et al, 2014). Therefore, T-ARMS-PCR is a reliable method for genotyping of SNP g.2885CNA within bovine ACADVL gene.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, 40% of the discrepancies between the two methods resulted from the PCR-RFLP incomplete digestion and the other 60% were the inaccuracies in sequencing of T-ARMS-PCR products . In the identification of mutations in IDH2 and DNMT3A, PCR-RFLP and ARMS methods showed a 100% concordance (Berenstein et al, 2014), and they also showed good uniformity in VDR genotypes in the sample of an Iranian population (Jafari et al, 2014). In the present study, the concordance between the two different methods was 98.76% (636/644).…”
Section: Discussionsupporting
confidence: 61%
“…Genomic DNA was extracted using Wizard Genomic DNA Purification kit (Promega Inc., Madison, WI, USA) according manufacturer's protocol. The VDR FokI T>C (rs 10735810), BsmI C>T (rs 1544410), ApaI G>T (rs7975232), and TaqI C>T (rs 731236) single nucleotide polymorphisms (SNPs) were determined by the Amplification Refractory Mutation System Polymerase Chain Reaction (ARMS-PCR) method using primers designed by Jafari et al (18). as presented in Table 1.…”
Section: Genotyping Of Vitamin D Receptor (Vdr) Polymorphimsmentioning
confidence: 99%
“…Genomic DNA extraction was done by Generation DNA Purification capture column kits (Fermentas, USA) from 200 µL of whole blood. The base sequences of the primers used for amplification-refractory mutation system polymerase chain reaction assay of VDR BsmI polymorphism were: 29 B′primer 5-′AGCCTGAGTACTGGGAATGT-3′;b′primer 5′-AGCCTGAGTACTGGGAATGC-3′;Consensus primer 5′-GGGAGGGAGTTAGGCACC-3′…”
Section: Methodsmentioning
confidence: 99%